PENGEMBANGAN MODUL PEMBELAJARAN KIMIA BERBASIS MULTIPEL REPRESENTASI PADA MATERI STOIKIOMETRI KELAS X SMAN 01 RASAU JAYA - Siti Assma; Raudhatul Fadhilah; Dini Hadiarti (Jurnal Ilmiah Ar-Razi, 2018)
Students’ understanding towards learning materials is generally influenced by the learning sources used. Lack of analytical skills and reasoning of the material taught especially stoichiometric material leads to a lack of interest in students' learning, students do not have a handbook but while learning takes place students use an inadequate number of textbooks in addition to covering only one or two representations. This study aimed to develop a learning module of multiple representation-based Stoichimetry concept. This study was a R &D method which adopting development of Brog & Gall. Sampling used purposive sampling. Subject in this research were students of class X IPA 2 as many as 9 students at initial field trials and 30 students of X IPA 1 at main field trials. Data collecting technique used were questionnaire and test. The data was analyzed by using Likert scale. The study revealed that the material validity by the material expert was 91,5%, and the validity by the media expert was 92,5%. The responses from the questionnaire on the practicality of the module were 88,17% and 86,89%. The effectiveness of the module could be seen from the students’ learning mastery value by 80,4%. In conclusion, the module that has been developed is considered feasible, practical, and effective to be used for both teachers and students in teaching learning process.Keywords: Stoichimetry Concept, Learning Module, Multiple Representation, Research and Development